Pregnancy outcome in a woman with congenital adrenal hyperplasia: a rare case report - Swamy, Mamatha; Ganesh, Divya; R., Ankitha C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Congenital adrenal hyperplasia (CAH) refers to family of inherited disorders of adrenal steroidogenesis caused by mutations in genes encoding steroidogenic enzymes involved in glucocorticoid synthesis/in cofactor enzyme P450 oxidoreductase that serves as electron donor to CYP21A2 and CYP17A1 with autosomal recessive inheritance pattern. A 24-year-old primigravida with simple virilizing CAH who underwent reconstructive surgery in childhood. During pregnancy, she developed severe preeclampsia requiring preterm emergency caesarean delivery at 30+6 weeks period of gestation. Stress steroid supplementation was administered intrapartum. Both mother and neonate had a favourable outcome with close multidisciplinary management. Early diagnosis, timely reconstructive surgery, optimized steroid replacement, and multidisciplinary care are crucial for favourable maternal and neonatal outcomes in CAH pregnancies.